Finding the train composition causing greatest fatigue damage in railway bridges by Late Acceptance Hill Climbing. (1st October 2019) - Frøseth, Gunnstein T.; Rönnquist, Anders
Highlights: Methodology to identify the most damaging train with respect to fatigue damage in railway bridges is presented. Exact solution can only be obtained for trivial cases. Late Acceptance Hill Climbing heuristic finds most damaging train efficiently. Abstract: This paper presents a method to identify the most damaging train with respect to fatigue damage in railway bridges. The problem is formulated as a combinatorial optimization problem in which the solution space is the set of possible trains. The exact solution can only be obtained for trivial cases where the train set is small and/or for simple structural details where the most damaging train can be identified manually by analysis. Three different heuristics are considered to solve the problem approximately. The Late Acceptance Hill Climbing heuristic is proposed as a general approach to finding the most damaging train due to its strong performance for different train sets and structural details and simplicity in implementation and application. The proposed methodology can be used in the design of new and in the assessment of existing railway bridges to verify sufficient fatigue endurance.